Staging the other: Orientalism in contemporary media practice - Jerrentrup, Maja Tabea (Arte, Individuo y Sociedad, 2021)
The so-called “oriental” has always been a subject for “western” fascination. Today, the staging of the “orient” in (hobby) model photography is among the most popular themes: costumes and props from various cultural contexts are combined to form a new whole. Based on participant observation and interviews, the article traces back possible individual motivations for embodying the “oriental,” among them nostalgia, corresponding with the description of the orient as “timeless,” the need for spirituality, the wish to express femininity, and to work on identity with regard to identity trials and the definition of the own identity through the help of its imagined opposite. Considering society as a whole and its zeitgeist, the phenomenon is interpreted using the concepts of escapism and kitsch, which can be observed in mainstream culture as well. Furthermore, cultural appropriation is discussed as a way to prevent getting to know other cultures, but at the same time, the “oriental” photoshoot is also seen as a chance to generate interest and to practice creativity. The article shows that the analysis of staged photographs offers a base for understanding the cultural context in which they have been taken and/or circulate, and that the photo motifs can be seen as expressions of psychological motivations.